Towards efficient designing of safe nanomaterials : innovative merge of computational approaches and experimental techniques - Leszczynski, Jerzy, 1949-; Puzyn, Tomasz (Cambridge : Royal Society of Chemistry, 2012)
Annotation The expanding field of nanotechnology is now one of the most promising areas of science. However, because some nanoparticles can have a negative impact on human health and the environment, the design of novel materials must always be accompanied by a comprehensive risk assessment. Until now, the information on the methods available has been fragmented and incomplete. This book is the first to provide a comprehensive review of recent progress and challenges in the risk assessment of nanomaterials by empirical and computational techniques.Topics covered include: benefits versus risks, carbon based nanomaterials, environmental detection and quantitative analysis, chemometric modelling, human exposure assessment, toxicity testing, nano-QSAR, risk assessment strategies, policy and regulatory frameworks.
Includes index.
Keywords: Nanostructured materials -- Design; Nanostructured materials -- Safety measures; Nanostructured materials -- Data processing